2021
DOI: 10.1039/d1ma00356a
|View full text |Cite
|
Sign up to set email alerts
|

Electrically driven formation and dynamics of swallow-tail solitons in smectic A liquid crystals

Abstract: Electric field driven instabilities of liquid crystals, such as electro-convections, spatiotemporal chaos, backflows, and solitons are of great importance for both fundamental science and practical applications. Here we demonstrate that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Experimentally, dissipative solitons were generated in the form of electric current filaments in a 2D planar gas-discharge system [98]. In LCs, different kinds of dissipative solitons have been generated and reported recently [99][100][101][102][103][104][105].…”
Section: Dynamic Dissipative Solitons In Liquid Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, dissipative solitons were generated in the form of electric current filaments in a 2D planar gas-discharge system [98]. In LCs, different kinds of dissipative solitons have been generated and reported recently [99][100][101][102][103][104][105].…”
Section: Dynamic Dissipative Solitons In Liquid Crystalsmentioning
confidence: 99%
“…So far, most dynamic solitons have been reported only in nematics. However, recently, it was shown that particle-like dynamic dissipative solitons can be formed in LCs of the fluid smectic A phase [104]. A smectic A phase is characterized by the formation of a layered structure of elongated molecules with orientational and 1D positional order.…”
Section: Dynamic Dissipative Solitons In Liquid Crystalsmentioning
confidence: 99%
“…6 Liquid crystals are anisotropic fluids with long-range orientational order of elongated molecules defined by the average of the long molecular axis called director, n. The study of solitons in liquid crystals was started in 1968 by Wolfgang Helfrich who theoretically modelled alignment inversion walls as static solitons in an infinite sample of nematic order. 7 Since then, different types of solitons have been reported, including different types of inversion walls, [7][8][9] propagating solitary waves, 10,11 individual convective rolls 12 and local convective domains, 13 discommensurations 14,15 and breathers, 16 nematicons, 17 directrons, 18 swallow-tail solitons 19 and others. In addition, a number of topological solitons, such as skyrmions, torons, hopfions, heliknotons are observed or created in chiral nematic liquid crystals (CNLCs).…”
Section: Introductionmentioning
confidence: 99%
“…In liquid crystals, three-dimensional solitons are typically observed near surface imperfections, dust particles, or electrode edges, traveling long distnces aperpendicular to the director field. , Initial observations of such solitons were made by P. Cladis and colleagues decades ago. More recently, several research groups have explored solitons from an experimental perspective, while others have considered various underlying theoretical aspects. …”
mentioning
confidence: 99%